POPULASI KEONG MAS (Pomacea canaliculata L.) DALAM UMPAN DAN JEBAKAN PADA TANAMAN PADI SAWAH (Oryza sativa L.) DI DESA GOLO BORE KECAMATAN NDOSO KABUPATEN MANGGARAI BARAT - Suriyati, Maria Enjelina; Sri Harini, Titik; Ludji, Rika; Kleden, Yasinta Letek (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
This research was carried out in Golo Bore Village, Ndoso District, West Manggarai Regency and took place from June to July 2023. The aim of this research was to determine the population of golden snails in baits and traps and the types of golden snails found in each treatment. This research method uses an experimental method with direct experiments in the field. This experiment used two treatments and five replications consisting of taro leaf bait (UDT) and water channel traps in the form of trenches (JSA). Observations were made at the age of the plants 21 days after planting. 28 days after planting and 35 days after planting. The research results in the bait treatment using taro leaves averaged 12 individuals and in the water channel trap treatment in the form of ditches 16.4 individuals. From this research, the gold snails found in the taro leaf bait (UDT) and water channel trap (JSA) treatments were the Pomacea canaliculata type with two different shell variations, namely striped and plain patterns.